Cross-domain collaboration: the Dutch Combined Lifestyle Intervention. (20th October 2021) - Bekker, M; Wagemakers, A
Abstract: Background: In the Netherlands, the policy-making process to realize funding for the Combined Lifestyle Intervention (CLI) by health insurance lasted twelve years. Since January 2019, the health care components of the CLI are covered by the Health Insurance Act. We aimed to identify policy design decisions, processes and implementation willingness and capacity of stakeholders. Methods: We conducted an institutional policy analysis using backward mapping. We composed a timeline (2007-2019) based on public documents and interviewed 22 key stakeholders, representing policy-making institutions, care professions, health insurers and CLI-owners. Results: Three main design decisions (out of 15) are: 1) including lifestyle coaching in the CLI.; 2) excluding the physical activity component for funding by health insurance and 3) health insurers and municipalities having own policies, resulting in a variety of contracts with health care providers and local differences in the CLI offer. Decision-making was mainly based on scientific evidence. However, not all stakeholders were represented in policy-making. The CLI requires collaboration between care professionals and lifestyle coaches, a new profession linking the medical and social domain. Vested and new stakeholders faced competing interests, which tempered their willingness and capacity to implement the CLI. Conclusions: The CLI sets a new standard - at the interface of indicated and selective prevention - by incorporating (non-medicalised) lifestyle coaching. Although the CLI is embedded in a single insurance-based scheme (instead of across domains), it institutionalizes cross-domain collaboration without providing the necessary resources. Collaborative prevention requires cross-domain trusting implementation networks, including vested stakeholders, field innovators and citizens, to avoid conflicts, and build adaptive and responsive prevention policies. Key messages: Interventions in the field of prevention require incentives for collaboration based on cross-domain trusting implementation networks. Politics around collaborative prevention requires a balanced stakeholder level playing field to avoid conflicts around vested interests and to facilitate stable responsive prevention policies.